2021
DOI: 10.1038/s41434-021-00302-5
|View full text |Cite
|
Sign up to set email alerts
|

A short hepatitis C virus NS5A peptide expression by AAV vector modulates human T cell activation and reduces vector immunogenicity

Abstract: Viral vector-mediated gene therapies have the potential to treat many human diseases; however, host immune responses against the vector and/or the transgene pose a safety risk to the patients and can negatively impact product efficacy. Thus, novel strategies to reduce vector immunogenicity are critical for the advancement of these therapies. T cell activation (TCA) is required for the development of immune responses during gene therapy. We hypothesized that modulation of TCA by incorporating a novel viral immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Transgene expression from weaker hepatocyte-specific promoters and RNAi-mediated transgene self-regulation [140][141][142] Avoid TLR 9 signaling activation CpG island reduction or TLR9 inhibition via oligonucleotide incorporation in the genome [143][144][145] Avoid dsRNA sensing Engineering of the expression cassette, such that transcription from 3 ITR is inhibited [146] Repress the activation of primary and memory T-cell responses Co-expressing NS5A with the transgene [147] Capsid Reduce dose, de-target APCs, and induce tolerance Rational designs and directed evolution to generate capsids with high hepatocyte transduction efficiencies [148][149][150][151] Avoid complement activation Rational designs and directed evolution to generate capsids that will evade pre-existing antibodies [135,[152][153][154] Avoid TLR9 signaling activation TLR9 inhibiting peptides insertion in the capsid [155] Reduce antigen presentation Mutation of surface-exposed tyrosine residues [156,157] Enhance Treg proliferation and reduce CD8+ T cell activity Incorporation of the MHC II epitopes derived from IgG in the AAV capsid [158] 11.…”
Section: Deplete Effecter T Cells and Induce Treg Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgene expression from weaker hepatocyte-specific promoters and RNAi-mediated transgene self-regulation [140][141][142] Avoid TLR 9 signaling activation CpG island reduction or TLR9 inhibition via oligonucleotide incorporation in the genome [143][144][145] Avoid dsRNA sensing Engineering of the expression cassette, such that transcription from 3 ITR is inhibited [146] Repress the activation of primary and memory T-cell responses Co-expressing NS5A with the transgene [147] Capsid Reduce dose, de-target APCs, and induce tolerance Rational designs and directed evolution to generate capsids with high hepatocyte transduction efficiencies [148][149][150][151] Avoid complement activation Rational designs and directed evolution to generate capsids that will evade pre-existing antibodies [135,[152][153][154] Avoid TLR9 signaling activation TLR9 inhibiting peptides insertion in the capsid [155] Reduce antigen presentation Mutation of surface-exposed tyrosine residues [156,157] Enhance Treg proliferation and reduce CD8+ T cell activity Incorporation of the MHC II epitopes derived from IgG in the AAV capsid [158] 11.…”
Section: Deplete Effecter T Cells and Induce Treg Expansionmentioning
confidence: 99%
“…A recent study showed that the AAV-mediated delivery of short immunomodulatory peptides, such as the hepatitis C virus non-structural protein 5A (NS5A), suppressed the unwanted activation of primary T-cells ex vivo. The expression of this proline-rich hydrophilic, 20-mer peptide represses the activation of memory T cell responses in the absence of CD3 (see Table 1) [147]. Designing anti-HBV AAVs that co-express this peptide may provide a strategy to overcome the anti-AAV adaptive immune response.…”
Section: Aav Genome Engineeringmentioning
confidence: 99%